PENERAPAN VISUAL SCHEDULEUNTUK MENINGKATKAN ACTIVITY OF DAILY LIVING SKILLPADA ANAK GANGGUAN SPEKTRUM AUTIS - Anwar Dani, Robik; Tyas Leylasari, Herdina (Widya Warta, 2020)
The objective of this research was to examine the effectiveness of visual schedule for increasing activity  of  daily  living  skill  of  children  with  autism  spectrum disorder.  Single-case  research method with A-B-A design was applied in this research. The subjects of the experiment was a seven-year-old  children  who  was  diagnosed  with  autism  spectrum  disorder.  An  activity  of daily living scale was used for data collecting in this experiment. The measurement was taken as   follows:   at   the   first   baseline,   the   treatment,   and   the   second   baseline.   Descriptive quantitative analysis method with graph trend analysis was used for data analysis. The result of  data  analysis  show  thatthere  is  an  increasing  in  the  activity  of  daily  living  scores  of  the subject.  In  conclusion,  the  visual  schedule  method  is  able  to  increase  activity  of  daily  living skill of children with autism spectrum disorder.